Mathematical Literacy Levels of Students in Solving AKM-Type Numeracy Problems Based on Rational and Artisan Personality Types - Fildza Claudia Saputri; Puguh Darmawan; Gwyneth B. Adaya (Universitas Negeri Surabaya, 2026)
Mathematical literacy is one of the important skills that students must have in order to deal with problems in daily life. Students' achievement of mathematical literacy can be affected by various factors, especially internal factors such as personality type. This study aims to analyze students' achievement of mathematical literacy in solving AKM numeracy problems based on rational and artisan personality types. This study used a descriptive qualitative method. The research subjects were 9 eighth-grade junior high school students with rational personality type and 8 students with artisan personality type. The instruments used were AKM numeracy test questions, Keirsey personality type questionnaire, interview guidelines, indicator rubrics, recording devices, and researcher notes. The data used were the subjects' written test results in solving AKM numeracy questions, researcher notes, and the results of interviews between the researcher and the subjects. The data analysis techniques used were data collection, data reduction, data presentation, and conclusion. The results of the study showed that subjects with the rational personality type were able to achieve mathematical literacy levels of one subject at level 4, one subject at level 5, and seven subjects at level 6. Meanwhile, students with artisan personality types achieved mathematical literacy levels of two subjects at level 3, two subjects at level 5, and four subjects at level 6. The main factor behind these differences in achievement is the thinking characteristics of each personality type. Another factor that also contributes to these differences in mathematical literacy levels is the learning experiences of each student.